Personal resources, work engagement and job burnout among Vietnamese ground employees in the aviation sector - Tung, Dao Duy; Ramasamy, Vijayan (Edelweiss Applied Science and Technology, 2025)
This study investigated the relationship between personal resources, work engagement, and job burnout among ground employees in the aviation sector. The research surveyed 250 ground employees who interacted face-to-face with passengers at check-in counters and during in-flight services. Data from 230 employees were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) to validate a conceptual model, with personal resources, work engagement, and job burnout measured as second-order variables within a hierarchical component model. The findings indicated that personal resources were significantly influenced by self-efficacy, optimism, resilience, and hope. Work engagement was significantly affected by vigor, dedication, and absorption. Job burnout was notably impacted by emotional exhaustion, cynicism, and reduced professional efficacy. The study demonstrated that personal resources serve as predictors of job burnout in the aviation sector, with work engagement functioning as a mediating variable. Importantly, the relationship between work engagement and burnout was found to be positively significant, suggesting that while work engagement can be beneficial, excessive levels may increase the risk of job burnout. The results emphasize the importance of enhancing personal resources among ground employees to mitigate job burnout, offering practical implications for managerial practices aimed at preventing human errors and ensuring flight safety.